Directional Control Mechanisms in Multidirectional Step Initiating Tasks - Inaba, Yuki; Suzuki, Takahito; Yoshioka, Shinsuke; Fukashiro, Senshi (Frontiers in Human Neuroscience, 2020)
Typical anticipatory postural adjustments (APAs) in forward gait or step initiation tasks to prepare for possible disturbances caused by prime voluntary movements and to accelerate the body forward have been previously reported. However, it is not clear how wide the variations in step directions are differentiated and controlled in non-forward step initiation tasks during the APA phase. The main goal of this study is to explain the directional control mechanisms by investigating the APA of step initiation tasks in forward, diagonal, lateral, and posterior directions. The center of pressure (COP) trajectories and related muscle (soleus, tibialis anterior, and gluteus medius of both lower limbs) activities during the APA of step initiation tasks in nine different directions were analyzed in six healthy young males. Posterior shifts of COP during APA decreased as the direction became more lateral (0° to 90°). For posterior step initiations, COP moved anteriorly from the initial position to accelerate the center of mass of the whole body (COM) backward. Lateral shifts of COP toward the stepping foot during APA decreased as the stepping direction became more lateral (from 0° to 45° and from 180° to 113°) while it plateaued to about zero in the direction from 45° to 113°. Both anteroposterior and lateral displacements of COP in APA were nonlinearly modulated to each direction, but they were linearly related to the anteroposterior and mediolateral component of the velocities of COM at take-off of the stance foot. Thus, the scaling of APA, reflected in the anteroposterior and lateral displacements of COP and the temporal sequence of selected muscle activities, was based on the anteroposterior and mediolateral components of the take-off velocity of COM that ultimately controls the direction of steps.